General organization of protein in HeLa 40S nuclear ribonucleoprotein particles (The Rockefeller University Press, 1985)
The majority of the protein mass of HeLa 40S heterogeneous nuclear ribonucleoprotein monoparticles is composed of multiple copies of six proteins that resolve in SDS gels as three groups of doublet bands (A1, A2; B1, B2; and C1, C2) (Beyer, A. L., M. E. Christensen, B. W. Walker, and W. M. LeStourgeon. 1977. Cell. 11: 127-138). We report here that when 40S monoparticles are exposed briefly to ribonuclease, proteins A1, C1, and C2 are solubilized coincidentally with the loss of most premessenger RNA sequences. The remaining proteins exist as tetramers of (A2)3(B1) or pentamers of (A2)3(B1)(B2). The tetramers may reassociate in highly specific ways to form either of two different structures. In 0.1 M salt approximately 12 tetramers (derived from three or four monoparticles) reassemble to form highly regular structures, which may possess dodecahedral symmetry. These structures sediment at 43S, are 20-22 nm in width, and have a mass near 2.3 million. These structures possess 450-500 bases of slowly labeled RNA, which migrates in gels as fragments 200-220 bases in length. In 9 mM salt the tetramers reassociate to form 2.0 M salt-insoluble helical filaments of indeterminant length with a pitch near 60 nm and diameter near 18 nm. If 40S monoparticles are treated briefly with nuclease-free proteases, the same proteins solubilized by nuclease (A1, C1, and C2) are preferentially cleaved. This protein cleavage is associated with the dissociation of most of the heterogeneous nuclear RNA. Proteins A2 and B1 again reassemble to form uniform, globular particles, but these sediment slightly slower than intact monoparticles. These findings indicate that proteins A1, C1, and C2 and most of the premessenger sequences occupy a peripheral position in intact monoparticles and that their homotypic and heterotypic associations are dependent on protein- RNA interactions. Protein cross-linking studies demonstrate that trimers of A1, A2, and C1 exist as the most easily stabilized homotypic association in 40S particles. This supports the 3:1 ratio (via densitometry) of the A and C proteins to the B proteins and indicates that 40S monoparticles are composed of three or four repeating units, each containing 3(A1),3(A2),1(B1),1(B2),3(C1), and 1(C2).